Modulation of Chirality and Intensity of Circularly Polarized Luminescence Emitting from Cholesteric Liquid Crystals Triggered by Photoresponsive Molecular Motor. Issue 3 (21st November 2021) - Bao, Jinying; Lan, Ruochen; Shen, Chen; Huang, Rui; Wang, Zizheng; Hu, Wei; Zhang, Lanying; Yang, Huai
Abstract: A chiral‐switchable device for circularly polarized luminescence (CPL) is fabricated based on dynamic superstructure of cholesteric liquid crystals (N*‐LC) doped with light‐driven molecular motor (MM), which achieves simultaneous modulation of chirality and intensity of CPL. Functional MM, designed with the modification of alkyl chains on the rotor, allows for advanced chemical isomerization to be driven with light. The selective reflection band due to the N*‐LC is shifted upon UV irradiation so that the reflection band moves toward the emissive band of the luminescence dyes, yielding CPL with opposite handedness and high dissymmetry factor values. The geometric changes of the motor during the rotary steps finally cause a remarkable reversible handedness inversion of the N*‐LC, which also leads switchable chirality of CPL. The dynamic N*‐LC cell bearing the light‐controlled selective reflection is useful for generating CPL from fluorescent materials and for allowing light chirality‐switching in CPL signals, which presents new possibilities for optoelectronic and photonics applications. Abstract : A novel molecular motor (MM) is designed with an ethylene glycol spacer modification on the rotor. Chiral‐switchable device presenting tunable circularly polarized luminescence (CPL) is fabricated based on the dynamic superstructure of cholesteric liquid crystals (N*‐LC) doped with the prepared light‐driven MM, which achieves the modulation of chirality and intensity of CPL.